Effect of Alchornea cordifolia Leaf Meal and Enzyme Supplementation on Growth, Haematological, Immunostimulatory and Serum Biochemical response of Rabbits - David, OLORUNTOLA Olugbenga; Olugbenga, AYODELE Simeon; Oluwasola, AGBEDE Johnson; Adebukola, OLORUNTOLA Deborah; Hilarious, OGUNSIPE Muyiwa; Samuel, OMONIYI Idowu (Asian Journal of Biological and Life Sciences, 2016)
The chemical compositions of Alchornea cordifolia leaf meal (ACLM) were determined. Thereafter, the effect of ACLM inclusion with enzyme supplementation on rabbits’ growth and health status was carried out in an eight weeks feeding trial. Six experimental diets were arranged in a 3x2 factorial arrangement i.e. 3 levels of ACLM inclusion (0, 50, and 100g/kg in place of palm kernel cake) combined with 2 levels of enzyme supplementation (0 and 0.35 g/kg). One hundred and eighty, five-week old rabbits were randomly allotted to six dietary treatments (10 replicate/treatment, 3 rabbits/replicate). The ACLM contained crude protein (180g/kg), crude fibre (129 g/kg), ash (12.8 g/kg), ether extract (41.2g/kg), nitrogen free extract (433g/kg), cardiac glycosides (0.14 mg/g), saponin (1.98 mg/g), phenols (1.21mg/g), phytate (1.08 mg/g), oxalate (1.30 mg/g), hydrogen cyanide (0.18 mg/g) and tannin (0.57mg/g). Potassium (76.00 mg/100g) was the most abundant mineral, while calcium, magnesium, iron, copper, zinc and manganese were also detected. Relatively, the weekly growth rate depression was recorded in diet 3 (10-E) throughout the feeding trial period. White blood cells, lymphocytes, monocytes and granulocytes decreased significantly (P<0.05) with increased ACLM levels. The urea, creatinine, cholesterol, bilirubin and serum glutamic oxalo acetic transaminase reduced (P<0.05) with increased ACLM level.
Keywords: Alchornea; Blood; Enzyme; Health status; Leaf meal; Rabbits; serum